Molecular and cellular aspects of Dutch elm disease - Sticklen, M.B.; Bolyard, M.G.; Hajela, R.K.; Dufresne, L.C. (Phytoprotection, 1991)
The folio wing review gives an overview of current research in the area of molecular and cellular interactions in Dutch elm disease. This vascular wilt disease is caused by the fungus Ophiostoma ulmi and is transmitted from diseased to healthy trees by the elm bark beetles. Fungal toxins are described which are associated with pathogenesis, one of which, ceratoulmin, is under investigation at the molecular level, particularly regarding its mode of action and localization. The fungus has also been examined at the molecular level to differentiate between aggressive and non-aggressive isolates on the basis of protein and nucleic acid profiles. Genetic linkage maps are being developed to correlate disruption of certain genes with the loss of pathogenicity. Viral and bacterial antagonists of the fungus, which may serve as biological control mechanisms for Dutch elm disease, have been characterized, as have several of the active molecules responsible for control. Host responses are also discussed at the molecular and biochemical level, including phytoalexins and defense mechanism elicitors. Several Unes of investigation are discussed to provide an overview of molecular approaches to understanding and manipulating the organisms involved with the ultimate goal of controlling Dutch elm disease.